Moel-Y-Gaer (Bodfari) - Lock, Gary (Archaeopress, 2022)
Moel-y-Gaer (Bodfari) is the northernmost of a series of hillforts atop the Clwydian hills in Wales. Nine seasons of survey and excavation reveal details of Moel-y-Gaer's ramparts, entrances and interior. Discussion situates the site within the later prehistoric settlement record for north-eastern Wales paying particular attention to hillforts.